Design and Development of a Fixed Asset Inventory System At The Holy Family Parish Church Atmodirono - Robertus Firenza Nugroho de Rozari; Albertus Dwiyoga Widiantoro; Andre Kurniawan Pamudji (Journal of Business and Technology, 2026)
The management of fixed assets at The Holy Family Parish Church Atmodirono is still carried out manually using Microsoft Excel, which causes various problems such as limited multi-user access, the risk of data duplication, recording errors, and difficulties in asset tracking and reporting. This study aims to design and build an integrated web-based fixed asset inventory system. The system development method used is the Waterfall method, which includes the stages of requirements analysis, system design, implementation, and testing. The system is built using the Laravel framework and MySQL database. The results of the study show that the developed system is able to improve the efficiency of asset management through centralized recording, asset tracking using QR Codes, and automatic reporting features.